PLACE AND ROLE OF THE JOURNAL SPORT SCIENTIFIC AND PRACTICAL ASPECTS IN THE DEVELOPMENT OF KINESIOLOGY - Almir Atiković (Sport Scientific And Practical Aspects, 2025)
The history of the Faculty of Physical Education and Sports dates back to 1945, when the first Teacher'sSchool was started at the end of the Second World War in Tuzla. From the activities of this school in 1960 came the Higher Pedagogical School in Tuzla within which the Department of Physical Culture was formed. In 1970, this school grew up in the Pedagogical Academy, and among the existing departments at the Pedagogical Academy, and there was a branch of Physical Culture. Since 1993, this department has been part of the newly formed Faculty of Philosophy in Tuzla. The Faculty of Physical Education and Sports was formed in 2003. The need for launching the journal "Sport - Scientific and Practical Aspects" for the purpose of successful work and action in past, proves that scientific thought, knowledge interprets and promotes through progressive reality. Visioning of the former management led by Ferhat Nožinović, Branimir Mikić, Vlatko Šeparović, Alen Kapiđić was reflected in the fact that we can say that we have created their own staff and now we are proud that we are one of the few faculty at our University that there is no need for hiring professors from the side and has the youngest and most promising scientific and professional staff. It is not our intent or desire to impress our achievements, but to open the door to inventiveness and creativity in the field of physical education and sports, and to promote scientific orientation and practical work in this area. Our experience shows that every institution or individual succeeds or does not succeed in life or the activity it deals with, depending on how much it is able to promote its values. In line with the global changes that are happening in higher education and our society, the mission of the Faculty of Physical Education and Sports in Tuzla can be seen through scientific research work, which also relies on publishing activities in the form of scientific and professional journals and workshops with symposium. The Faculty of Physical Education and Sports of the University of Tuzla is an institution which, in addition to the education of professional and scientific personnel in the field of physical and medical education and sport, is engaged in the provision of professional work services both with top athletes andrecreationalists. Since we are the only institution of this type in the region (Tuzla canton) our service is used by all sports clubs and individuals involved in all aspects of organized, sporting or sport-recreational activities of our Tuzla canton. The scientific and research work at the Faculty of Physical Education and Sports of the University of Tuzla is carried out at the faculty, where there is a separate space and equipment, as well as in the Institute of Sports Medicine of the Health House "Mustafa Mujbegović" in Tuzla, where there is equipment and a skilled staff for diagnosing motor, functional abilities and rehabilitation. The Faculty of Physical Education and Sports of the University of Tuzla has equipment for testing and measuring the morphological characteristics, motor skills and situational and motor abilities of the respondents, the postural status of the respondents, and the planning and programming of the training process and other activities of a similar character. The Faculty of Physical Education and Sports of the University of Tuzla, from 2004 to 2008, publishes a scientific and professional journal "Sport - Scientific and Practical Aspects", published twice a year in Bosnian, Serbian andCroatian. The aim and intent of the journal is to increase theoretical and practical knowledge in the field of sports and kinesiology in general and to enable all scientific workers and expertsin this field to promote their work and to publish their new knowledge of their work. The paper publishes works that are divided into several sections. Sport Scientific And Practical Aspects is an international journal of sport science and kinesiology. The journal publishes scientific, theoretical and empirical articles and other written material related to following kinesiology fields: Biomechanics, Kinesiology Assessment,Training Theory, Management in Sport, Physical Education, Methodology, Statistics and ResearchMethods, Sport and Health, Adaptive Physical Activity, Sport Medicine, etc. The aim and intention of the journal is to increase theoretical and practical knowledge of above mentioned kinesiology fields, to enable and encourage young researchers to publish their articles and to provide practical information, useful for kinesiology practitioners, coaches, PE teachers, athletic trainers, physical therapists and athletes. The journal generally accepts original scientific papers, review articles, but takes in consideration meta- analysis, case studies, brief reports, narrative reviews, professional papers, commentaries and letters to editors. The journal from 2008 begins to be published in English, with abstracts in English and Bosnian / Croatian / Serbian language, and is thus transformed into an international journal recognizable in the region and world. According to the said journal, the title "Sport Scientific and Practical Aspects" is also changed from Bosnian to English language. About journal editing takes account of journal management, international editorial board, advisory and review committee, and section editors. The results of scientific research of the kinesiologist are published in the journal Sports Scientific and Practical Aspects pod brojem (UDK: 796, print ISSN 1840-4413, online ISSN 1840-4561). The journal is referenced in the following databases: COBISS BH, CAB Abstracts, Physical Physical Education Index, Genamics Journal Seek, Open J-Gate, EBSCO Sportdiscus, DOAJ, Electronic Journals Index, Index Copernicus, getCITED, Google Scholar Beta, Scirus, NewJour, Elsevier's EMCare database. Frequency (annually): twice. Review takes place as follows: external reviewers, mostly overseas, double, scientific and professional papers, double-blind. Rights of Use: The journal is available in an open access. All works published in this journal may be used free of charge for personal, educational or scientific purposes without violating the copyrights of authors and publishers. Management: Editor-in-Chief Vlatko Šeparović (Tuzla University, Bosnia and Herzegovina); Associate Editors-in-Chief Monèm Jemni (University of Greenwich, United Kingdom), Edin Užièanin, Almir Atiković, Edin Mujanović (Tuzla University, Bosnia and Herzegovina); Scientific Consultants: Milan Čoh (University of Ljubljana, Slovenia), Ekrem Čolakhodžić (University Džemal Bijedić, Bosnia and Herzegovina), Haris Pojskić (Mid Sweden University, Sweden); Young Editor Fuad Babajić (Tuzla University, Bosnia and Herzegovina). We would like to express our special gratitude to our founders who have been acclaiming the journal all these years and have been raising their quality on a daily basis with their knowledge, reputation and work.